Domestic Violence (Kekerasan Dalam Rumah Tangga) Dalam Perspektif Kriminologi dan Yuridis - Harkrisnowo, Harkristuti (Indonesian Journal of International Law, 2021)
Domestic violence is one shape of violence that happened to certain women in the world. The major cause of this type of violence is discrimination against women as one of gender issues. Actually, problem of women's discrimination has been addressed in several law instruments, both national and international. Domestic violence is obstinate to restrain in society and is difficult to bring up to the surface for the reason that there is power relationship between victim and offender besides emotional relationship and psychological burden. This recent day, Indonesia attempts to develop a draft of national rule for protecting women from domestic violence, which called Draft on Domestic Violence Law. Unfortunately, this draft still has some lack that can raise new problems in its implementation. This article explains about a whole picture of domestic violence, the critics towards Draft on Domestic Violence Law, and alternative solution to manage problems in domestic violence.